Shale gas production processes - Speight, James G. (Gulf Professional Publishing, an imprint of Elsevier, 2013)
This book provides an overview of the chemistry, engineering, and technology of shale gas, including new and evolving process technologies and their applications as well as environmental regulations. It also discusses methods used to reduce environmental footprint and improve well performance.